Establishment of the possible association between the presence of Helicobacter pylori in the saliva and gastric biopsy by using polymerase chain reaction technique in association with oral manifestation of peptic ulcer disease - Thamer, Sabaa R; Al-Ani, Sahar (Journal of Baghdad College of Dentistry, 2015)
Background: Helicobacter pylori are important gastrointestinal pathogen associated with gastritis, peptic ulcers, and an increased risk of gastric carcinoma. There are several popular methods for detection of H. pylori (invasive and non-invasive methods) each having its own advantages, disadvantages, and limitations, and by using PCR technique the ability to detect H. pylori in saliva samples offers a potential for an alternative test for detection of this microorganism. Materials and methods: The study sample consists of fifty participants of both genders, who undergo Oesophageo-gastrodudenoscopy at the Gastroenterology Department of Al-Kindy Teaching Hospital Baghdad/ Iraq, during five months period from January 2014 to May 2014. They were grouped into 32 participants with PUD (case group) and 18 healthy participants (control group). A full-mouth examination was performed for every patient; saliva and gastric samples from both groups were obtained. Helicobacter pylori were detected in gastric biopsies by histological examination by using H & E stain, and Polymerase Chain Reaction (PCR) was carried out on the oral samples. Results: Helicobacter pylori DNAwas determined by PCR in oral samples in 88% patients and in gastric biopsies by histology in 86% patients, and in both samples in 84% patients.It was highly significant to find simultaneous presence for those have H. pylori in stomach also have such microorganism in the mouth P < 0.05 and there was an excellent correlation between detecting H. pylori simultaneously in both stomach and mouth. If we screen for stomach H. pylori through detecting this microorganism in the mouth; saliva samples is highly sensitive (98%) but not very specific. Conclusion: Helicobacter pylori saliva test has high sensitivity, specificity, and accuracy for the diagnosis of H. pylori infection in Iraqi population. The test can be clinically applied as a routine diagnostic tool for H. pylori infection this could permit not only a target for therapeutic procedures but also a monitoring tool for the efficacy of therapy. It seems to overcome some limitations of the conventional invasive techniques.